PENANAMAN NILAI-NILAI KEISLAMAN UNTUK MEMBENTUK KARAKTER SISWA MELALUI PEMBELAJARAN SEJARAH KEBUDAYAN ISLAM (SKI) - Munawir, Munawir; Negari, Beauty Dewi; Ta’dzimah, Imamatut (Ibn Khaldun University, Bogor, 2023)
Character education is an effort or action that is carried out intentionally and planned to help someone so that that person can understand, pay attention to, and implement true ethical values so that he can become a useful individual. One way to shape student character is through inculcating Islamic values in Islamic Cultural History (SKI) subjects. The purpose of this research is that madrasa students can have good character education and uphold Islamic values through learning Islamic Cultural History which has been taught in madrasas. This research uses the method of literature study or library research. The result of this study is that Islamic cultivation to shape student character can be done through Islamic Cultural History (SKI) subjects because the material in this subject is very complex including the history of past events where we can emulate the attitude of role models in the present.